Relationships among perceived social support, mindful self-care, and resilience among a sample of nurses in three provinces in China: a cross-sectional study - Li, Meng; Wei, Junfan; Yang, Shuhua; Tian, Yuan; Han, Shan; Jia, Guanhu; De Ala, Minerva; Song, Ruipeng; Wei, Bo (Frontiers in Public Health, 2024)
Objective In this study, we aimed to determine the relationships among perceived social support, mindful self-care, and resilience in a sample of nurses in three provinces of China. Methods A cross-sectional study was conducted in seven hospitals in Guangdong, Guizhou, and Henan provinces between August and October, 2023; the provinces are located in south, southwest, and central China. A total of 389 nurses were surveyed using a self-designed sociodemographic characteristics questionnaire and the Chinese versions of Multidimensional Scale of the Perceived Social Support, Brief-Mindful Self-Care Scale and the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). Results Of the 389 nurses, the majority were women (n = 365; 93.8%), aged 26–35 years (n = 244; 62.7%) and had bachelor’s degrees (n = 337; 86.6%), had worked for 10–20 years (n = 136; 35%), with junior professional titles (n = 331; 85.1%), and had a monthly income in the range 3,001–6,000 yuan in CNY (n = 239; 61.4%). Nurses’ resilience was measured using the CD-RISC-10, which ranges from 10 to 40 points. And average score of nurses’ resilience was (23.94 ± 6.95). Multiple linear regression showed that scores for resilience were higher among nurses who had higher educational attainment (95% confidence interval: 0.568–3.024, p < 0.01), professional titles (95% confidence interval: 0.009–1.693, p < 0.05), scores of mindful self-care (95% confidence interval: 0.086–0.155, p < 0.01), and scores of perceived social support (95% confidence interval: 0.242–0.328, p < 0.01). Conclusion Nurses with higher educational attainment and professional titles exhibited higher levels of resilience. Perceived social support and mindfulness self-care are significantly positively correlated with resilience of nurses. The findings of this study are beneficial to further our understanding of nurses’ resilience. The identification of associated factors is conducive to providing more support for nurses who tend to have lower resilience earlier, and can provide useful information for research targeted intervention and support plans aimed at improving nurses’ resilience in the future.